ANALISIS VIBRASI PADA GENERATOR SINKRON (STUDI KASUS PADA PLTU KALTIM 2 x 110 MW) - suratno . (Lembaga Penelitian Universitas Balikpapan, 2020)
Damage of using a synchronous machine in a power plant cannot be avoided especially when there is vibration produced by the machine. The loss incurred may lead to significant losses in the production process. Though maintaining an electrical machine in ideal condition is preferred, defect in machine fabrication cannot be avoided. Those defects may lead to friction between moving parts and produce vibration on the machine. Thus, to reduce losses and control the vibration of the system, vibration analysis of the device need to be done. For the reasons mentioned above, the author attempts to analyze the vibration as well as to minimize the losses incurred in the case of vibration exceeding the normal threshold. Predictive maintenance is expected to occur due to vibration disturbance in the generator. The research was carried out in PLTU Kaltim Teluk Balikpapan 2 x 110 MW. The analytical method used in this analysis is first, the monitoring method condition, which monitors the state of the engine through the data captured. Secondly, comparing the data obtained with the previous data to observe the changes occurring in the device. Lastly, analyzing the vibration categories based on ISO standard vibration (ISO 7919). From the operation data, alteration in the generator load will affect the temperature and vibration of the alternator. With a higher load, the vibration and temperature of the rotary generator will also have a higher value. By displaying the higher-direction vibration data of 131.7 μm with a load of 59.6 MW and a temperature of 64.6 ° C. From observation and data analysis, it is concluded that due to the uneven distribution of temperature in the rotor, synchronous generators undergo reversible thermal sensitivity symptoms.